Keys Under Doormats. - Abelson, Harold “Hal”; Anderson, Ross; Bellovin, Steven M.; Benaloh, Josh; Blaze, Matt; Diffie, Whitfield “Whit”; Gilmore, John; Green, Matthew; Landau, Susan; Neumann, Peter G.; Rivest, Ronald L.; Schiller, Jeffrey I.; et al. (Communications of the ACM, 2015)
The article presents the opinions of a number of computer scientists and computer security experts concerning law enforcement access to electronic devices and computer systems. The authors mention a debate that took place in the 1990s concerning a proposed Clipper Chip, which would have allowed law enforcement agencies to have "back door" access to computers and computer devices. The authors argue that the idea of building systems with an approved method to access computers presents unacceptable security risks.